EVALUASI KINERJA POLITISI PEREMPUAN ANGOTA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN SINJAI - Dedi; Khaerah, Nur; Hardi, Rudi (Government Studies Departement of Universitas Islam Majapahit, Indonesia, 2021)
This article discusses the performance of female politicians from the Sinjai Regency Regional People's Legislative Council. research methods thatused is a type of qualitative descriptive research. There are 7 informants using data collection techniques throughinterviews, observations and documentation. The research data analysis technique is through the stages of data simplification, data analysis, and data verification.The results of this study indicate that the performance of female politicians in the DPRD of Sinjai Regency in 2014-2019 has been good, it can be seenfrom the implementation of the role of women politicians in carrying out the function of legislation, as evidenced by the successful approval of regional regulations related togender, and children. Women politicians are judged to be able to recognize the needs and aspirations of the community to then be poured into policies. BesidesTherefore, the implementation of the role of women politicians in carrying out the budget function can be seen from the success in determining the amount of the budget forsupport programs to increase women, women politicians are considered active and capable in carrying out supervisory functions, includingsupervising the executive, supervising the running of the government and carrying out supervision of the APBD by the SKPD.